2009
DOI: 10.1055/s-0029-1217146
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Organocatalytic Quadruple Domino Reactions of Acetaldehyde and Nitroalkenes

Abstract: A microwave-assisted, organocatalytic domino Michael/ Henry condensation/Michael/aldol condensation reaction has been developed. Employing acetaldehyde and nitroalkenes as substrates, this quadruple cascade allows an efficient asymmetric synthesis of trisubstituted cyclohexene carbaldehydes in moderate to good yields (25-45%) and high enantioselectivities (ee = 89 to >99%). ESI-MS measurements were carried out to support the proposed complex catalytic cycle.Over the last decade the area of organocatalysis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…[20] This type of activation has been described recently in different types of organocatalyzed asymmetric reactions with the aim of shortening reaction times and catalyst loadings. [21] We found that microwave irradiation had a positive effect on the reaction time and retained very good yields and selectivities. When the reaction was performed in chloroform at 80 8C, a 90 % ee and a 91 % yield were achieved in only 30 min (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 73%
“…[20] This type of activation has been described recently in different types of organocatalyzed asymmetric reactions with the aim of shortening reaction times and catalyst loadings. [21] We found that microwave irradiation had a positive effect on the reaction time and retained very good yields and selectivities. When the reaction was performed in chloroform at 80 8C, a 90 % ee and a 91 % yield were achieved in only 30 min (Table 1, entry 17).…”
Section: Resultsmentioning
confidence: 73%
“…A Michael/Henry/condensation/Michael/aldol condensation with nitroolefines and acetaldehyde 30 in the presence of diphenylprolinol derivative 87 was reported by Enders et al [267] Highly substituted chiral cyclohexene carboxaldehydes were isolated under microwave conditions (Scheme 137).…”
Section: Wwwchemeurjorgmentioning
confidence: 98%
“…[155] Employing amine (S)-3 as the catalyst, three equivalents of acetaldehyde reacted with nitroalkenes according to a quadruple cascade to afford the corresponding trisubstituted cyclohexenecarbaldehydes 341a-e in moderate to good yields (25-45%) and good to high enantioselectivities (89 to > 99% ee) combined with a general diastereoselectivity of > 96% de, as shown in Scheme 90. The authors have proposed the mechanism depicted in Scheme 90 in which the cascade started with the enamine activation of acetaldehyde by the catalyst and Michael addition to the nitroalkene.…”
Section: Michael Reaction Of Nitroolefinsmentioning
confidence: 99%